Correction: Efficient triplet–triplet annihilation upconversion in binary crystalline solids fabricated via solution casting and operated in air. Issue 6 (22nd August 2018) - Kamada, Kenji; Sakagami, Yusuke; Mizokuro, Toshiko; Fujiwara, Yutaka; Kobayashi, Kenji; Narushima, Kaishi; Hirata, Shuzo; Vacha, Martin
Abstract : Correction for 'Efficient triplet–triplet annihilation upconversion in binary crystalline solids fabricated via solution casting and operated in air' by Kenji Kamada et al., Mater. Horiz., 2017, 4, 83–87.